1980
DOI: 10.1079/bjn19800063
|View full text |Cite
|
Sign up to set email alerts
|

The use of common salt (sodium chloride) fortified with iron to control anaemia: results of a preliminary study

Abstract: 1. Iron-deficiency anaemia continues to be a major public health problem in all developing countries. Fortification of commonly consumed food items has been suggested as an effective method of preventing anaemia. Common salt (sodium chloride) has been identified as a suitable vehicle to be fortified with Fe in India. 2. Common salt was fortified with ferric orthophosphate (3500 mg/kg) and sodium hydrogen sulphate (5000 mg/kg) to provide an additional 1 mg elemental Fe/g common salt consumed. 3. After ascertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…When the particle size is smaller, the iron absorption is higher, but the product is also much more expensive. 17,19,24,[31][32][33][34][35][36][37] Whitaker reviewed the use of some iron compounds in food forti cation. 10 He concluded that the use of elemental iron to fortify foods increased because it is inexpensive to produce and because organoleptic problems associated with it are minimal.…”
Section: Iron Compoundsmentioning
confidence: 99%
“…When the particle size is smaller, the iron absorption is higher, but the product is also much more expensive. 17,19,24,[31][32][33][34][35][36][37] Whitaker reviewed the use of some iron compounds in food forti cation. 10 He concluded that the use of elemental iron to fortify foods increased because it is inexpensive to produce and because organoleptic problems associated with it are minimal.…”
Section: Iron Compoundsmentioning
confidence: 99%
“…The major part of salt production is confined to two or three states in India and a well-defined distribution and monitoring machinery is in place. Technology for production of iron fortified salt (Narasinga Rao & Vijayasarathy, 1975;Narasinga Rao & Vijayasarathy, 1978;Nadiger et al 1980; Report of the Working Group on Fortification of Salt with Iron, 1982) and iodine and iron fortified salt has been developed in India mainly through the efforts of National Institute of Nutrition (Narasinga Brahmam et al 1994;Ranganathan et al 1996;Nair et al 1998a;Nair et al 1998b).…”
Section: Technology Of Food Fortification In Indiamentioning
confidence: 99%
“…Many experiments on food fortification have been conducted in developing countries. These include fortification of sugar in Guatemala (Viteri et al 1995a), fish sauce in Thailand (Garby & Areekul, 1974), curry powder in South Africa (Ballot et al 1980), and salt in India (Nadiger et al 1980; Working Group on the Fortification of Salt with Iron, 1982). The experiments reported favourably in terms of acceptability by the target population as well as improving their iron status.…”
Section: F O O D F O R T I F I C a T I O Nmentioning
confidence: 99%